CRISIS MANAGEMENT STRATEGY OF PUBLIC RELATION PTPN-V RELATED TO COMPANY’S CONFLICT WITH SOCIETY (Study On The Estate Limited Plantation Nusantara V Sei Kencana Garden Tapung Hulu District Of Kampar) - Epiyani Sembiring; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Crisis management strategy is one of the tasks when the company's public relations practitioners in crisis. Public relations strategy must be used by public relations to solve the problems being faced by an organization or institution. The emergence of negative news through the mass media both print and electronic media about the PTPN-V related conflicts between company and society can provide negative public reaction to the company in response to the media coverage. Therefore company needs crisis management strategy to resolve the conflict. This research aims to determine the public relations strategy of PTPN-V in identifying the issues that caused the crisis, to find out the public relations strategy of PTPN-V in mapping the needs of journalists, and to find out the public relations strategy of PTPN-V in preparing information for the management of related conflicts between company and society.The research method that was chosen in this study is a qualitative method to explain the phenomena that occur in accordance with the results was obtained by defining five (5) subjects research through purposive sampling and the object of this study is the crisis management strategy PTPN-V-related conflicts between companies and societyand the data is based on information obtained through observation and interviews as well as maximize the documentation method to collect data. Technical analysis of the data that was used is model of interactive data with data validity checking is done by using the extension of participation and triangulation techniques.The results showed that the crisis related to the conflict between the company and society can be solved well. Publicist of PTPN-V identifying the issues that led to the crisis by deepening the data and facts and then made the press conference and gave a press release to the media. Crisis management strategy of public relation PTPN-V focused to the media in resolving the conflict with fourth phases namely, a phase of crisis management preparation, response, recovery, and mitigation. Information that was given to the management about a contingency plan public relation of PTPN-V in working during the crisis is to focus on the mass media and execute media relations then make an evaluation for following-up.Keyword: PTPN-V, Conflict, Crisis Management Strategy, Public Relations Strategy